THE ANALYSIS OF THE APPLICATION OF ACCOUNTING INFORMATION SYSTEM MERCHANDISE INVENTORY AT PT. HASJRAT ABADI BRANCH TENDEAN - Palandeng, Olfiani E.; Karamoy, Herman (Universitas Sam Ratulangi, 2015)
THE ANALYSIS OF THE APPLICATION OF ACCOUNTING INFORMATION SYSTEMÂ MERCHANDISE INVENTORY AT PT. HASJRAT ABADI BRANCH TENDEAN